Robust Multi-Objective Optimization Model for the Integration of Blood Production and Distribution Planning - Shearly Christina Tanjung; Eric Wibisono; Dina Natalia Prayogo (Jurnal Ilmiah Teknik Industri, 2023)
Blood is a very important element for humans. Currently, The Blood Transfusion Unit of The Indonesian Red Cross in City “X” determines the amount and type of blood to be processed based on stock availability. This method tends to be subjective so that the possibility of error in production decision is fairly high. This research intends to manage that the blood processing process and allocation can be carried out optimally and on target. The research objectives are to minimize the number of blood shortages, expired blood, and the total costs incurred, by applying a robust optimization method that considers the uncertainty of blood demand and the disturbances in the blood production process. Pass data of demands will be used for forecasting demand in the planning period. The forecast results can be adjusted to current conditions using the adjustment ratios. The robust optimization method can produce decisions that tend to be stable even when there are changes in blood demand. The results obtained in this study were 24% decrease in the number of shortages of blood stock, 88% decrease in the amount of expired blood, and 96% decrease in the overproduction cost.